Clinical Benefit of Comprehensive Genomic Profiling for Advanced Cancers in India. (11th April 2022) - Mathew, Aju; Joseph, Serena; Boby, Jeffrey; Benny, Steve; Veedu, Janeesh; Rajappa, Senthil; Rohatgi, Nitesh; Sirohi, Bhawna; Jain, Reetu; Agarwala, Vivek; Shukla, Deepak Kumar; Mehta, Anurag; et al.
Abstract : PURPOSE: Comprehensive genomic profiling (CGP) assay is increasingly used in low-middle–income countries to detect clinically relevant genomic alterations despite its clinical benefits not being well known. Here, we describe the proportion of patients with advanced cancer in India who received targeted therapy for an actionable genetic alteration identified on CGP assays. METHODS: This was a multicenter, retrospective cohort study in adult patients with advanced nonhematologic malignancies who underwent a CGP test. If patients received a targeted therapy for ≥ 6 months, they were considered to have obtained a clinical benefit from the medication, whereas those continuing for ≥ 12 months were considered to have attained an exceptional response. Descriptive statistics were used to describe the proportion of patients with subsequent targeted therapy. RESULTS: During 2019-2020, 12 medical oncologists provided CGP reports for 297 patients; 221 met the inclusion criteria. Patients received a median of two lines (range: 0-5) of prior systemic therapy. On the basis of the CGP assay, 21 patients (10%) received targeted therapy. Among them, 33% was for human epidermal growth factor receptor 2 (HER2) amplification (nonbreast cancer) and 19% for HER2 or epidermal growth factor receptor exon 20 insertion mutation (lung cancer). After excluding patients with HER2 or epidermal growth factor receptor exon 20 insertions, 8% of 217 patients received targeted therapy. In the overall cohort of 221 patients, clinical benefit was seen in nine patients (4%), of whom two were exceptional responders (1%). CONCLUSION: We observed that in a low-middle–income country setting, 10% of patients received targeted therapy on the basis of CGP assay. Only 4% of patients who underwent CGP testing obtained a clinical benefit. Abstract : Genomic profiling assay study from India showcases both the promise and limitations of testing in advanced cancers. 10% of patients who were tested got a targeted drug. 4% took it for at least 6 months.